Innovative Computing, Optimization and Its Applications Modelling and Simulations - Zelinka, Ivan; Vasant, Pandian; Duy, Vo Hoang; Dao, Tran Trong (Studies in Computational Intelligence, 2018)
This book presents the latest research of the field of optimization, modeling and algorithms, discussing the real-world application problems associated with new innovative methodologies. The requirements and demands of problem solving have been increasing exponentially and new computer science and engineering technologies have reduced the scope of data coverage worldwide. The recent advances in information communication technology (ICT) have contributed to reducing the gaps in the coverage of domains around the globe. The book is a valuable reference work for researchers in the fields of computer science and engineering with a particular focus on modeling, simulation and optimization as well as for postgraduates, managers, economists and decision makers.